Tantangan SDM dalam Kerja Multinasional antara Tenaga Kerja Asing dan Lokal di PT Real Soluplus Indonesia - Nur Fatikhah Denisa Ana Farizka (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study examines the challenges of human resource (HR) management in a multinational work environment involving both foreign and local workers at PT Real Soluplus Indonesia. The purpose of this study is to identify various obstacles that arise in cross-cultural HR management, analyze their impact on company performance, and evaluate strategies implemented to overcome them. The method used is a qualitative approach with a literature review, through the collection and analysis of various sources such as scientific journals, books, and previous research relevant to cross-cultural HR management. The results indicate that the main challenges include language differences, differences in work culture, difficulties in the adaptation process, and potential conflict between employees. These challenges result in decreased communication effectiveness, increased risk of miscommunication, and disrupted work productivity. To address these challenges, the company implemented various strategies such as cross-cultural training, improved communication effectiveness, work system adjustments, and inclusive multinational team management. The study concludes that effective multinational HR management is crucial for maintaining the stability of a company's operations. With the right strategy, workforce diversity can actually become a competitive advantage, improving a company's performance and competitiveness globally.